SKENARIO IMPLEMENTASI SISTEM INFORMASI IDENTITAS DIGITAL DENGAN MENGGUNAKAN WSO2 IS DI STMIK “AMIKBANDUNG”: Studi Kasus: STMIK “AMIKBANDUNG” - Andi Rahayu; Hermawaty Hermawaty; Muhammad Abdul Mujib; Rizal Dzulkarnaen (Journal of Information Technology, 2021)
The continued development of technology makes the number of applications used in various activities. Most users use different kinds of credentials (username and password) to log into the various available application services. Based on the problem, the Single Sign On (SSO) system is proposed for user authentication, where users can access several applications without having to log in to each application. In the application of SSO, WSO2 IS is used as an Identity Provider where this server application facilitates security when connecting and managing multiple identities in various applications. In its development, an application that acts as a Service Provider (the part that requires authentication) is also made with various protocols such as SAML and OPENID. The results of implementing SSO using WSO2 IS and applications with SAML and OPENID protocols succeeded in making the system allow users to access all resources in the network using only one credential.. Keywords— Credential, Single Sign On, WSO2 IS , SAML, OPENID..